Analisa Pembatalan Perkawinan Poligami Akibat Pernyataan Palsu: Studi Kasus Putusan Nomor 2530/Pdt. G/2019/PA.Mdn - Siti Nurhaliza Dalimunthe; Mia Hadiati (LPPM Universitas Ekasakti Padang, 2023)
This research aims to analyze cases of cancellation of polygamous marriages due to false statements, with a focus on Case Study Decision Number 2530/Pdt. G/2019/PA.Mdn. The research background involved a lawsuit filed by a man regarding the marriage of Defendant I and Defendant II which was carried out without the knowledge of the Plaintiff as the legal guardian. The research method used is normative qualitative by collecting secondary data from relevant laws and judicial decisions. The results of the research show that the marriage of Defendant I and Defendant II was declared null and void because they did not meet the requirements for a legal guardian, which was linked to the Plaintiff's disagreement as the biological father of Defendant I. This analysis is based on Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law , and supported by documentary evidence such as a marriage certificate. The research conclusion confirms that court decisions reflect the judge's thoroughness in implementing applicable legal provisions, protecting individual rights, and upholding the validity of marriage. These results contribute to the development of legal precedent regarding the annulment of polygamous marriages due to false statements in the future.